CHOLINESTERASE INHIBITORS IN THE TREATMENT OF DEMENTIA ALZHEIMER’S - Primaniar S, Prameidya (E-Jurnal Medika Udayana; vol 2 no3 (2013):e-jurnal medika udayana)
Dementia is the loss of intellectual abilities which include decreased ability to think, remember, understand, calculate, concentrate, and find the right words. The causes of dementia are Alzheimer’s, vascular dementia, alcohol. Dementia Alzheimer’s is a dementia type that is currently the most commonly found. Cholinesterase inhibitors are one of the therapies used to treat symptoms of cognitive decline and reduce neuropsychiatric symptoms in patient dementia Alzheimer’s. Several studies have been conducted to demonstrate how the effects of several classes of cholinesterase inhibitors in the treatment of dementia Alzheimer’s. Effective dose, dosage and side effects of cholinesterase inhibitors is important to know before deciding to use cholinesterase inhibitors in the treatment of dementia Alzheimer’s.
Keywords: cholinesterase inhibitors, dementia Alzheimer’s